2012
DOI: 10.1002/14651858.cd006726.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Psychological therapies for the treatment of post-traumatic stress disorder in children and adolescents

Abstract: There is evidence for the effectiveness of psychological therapies, particularly CBT, for treating PTSD in children and adolescents for up to a month following treatment. At this stage, there is no clear evidence for the effectiveness of one psychological therapy compared to others. There is also not enough evidence to conclude that children and adolescents with particular types of trauma are more or less likely to respond to psychological therapies than others.The findings of this review are limited by the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
56
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(63 citation statements)
references
References 110 publications
5
56
1
1
Order By: Relevance
“…The proportion of cognitive behavioral interventions found to be superior to a control condition was not significantly different than the proportion of non cognitive behavioral interventions that were superior to a control condition. This is consistent with the conclusion of Gillies and colleagues [48] in their Cochrane Review on the treatment of PTSD in children that, while there is "fair evidence for the effectiveness of psychological therapies," especially cognitive behavioral interventions, there is "no clear evidence" that any one therapy is superior to others (p. 21).…”
Section: Efficacy Of Intervention Approaches and Intervention Componentssupporting
confidence: 86%
“…The proportion of cognitive behavioral interventions found to be superior to a control condition was not significantly different than the proportion of non cognitive behavioral interventions that were superior to a control condition. This is consistent with the conclusion of Gillies and colleagues [48] in their Cochrane Review on the treatment of PTSD in children that, while there is "fair evidence for the effectiveness of psychological therapies," especially cognitive behavioral interventions, there is "no clear evidence" that any one therapy is superior to others (p. 21).…”
Section: Efficacy Of Intervention Approaches and Intervention Componentssupporting
confidence: 86%
“…Although evidence-based trauma- focused treatments are available [2], many children and adolescents with PTSD or other trauma-related disorders do not receive appropriate care. This was recently demonstrated when survivors of child sexual abuse reported on their experiences to the Independent Commissioner mandated by the German Federal Government to develop a societal agenda to improve prevention and intervention programs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Tf-CBT is the most frequently investigated treatment, with a total of 11 RCTs up to 2014 [7,8]. The methodical limitations of previous studies of psychological therapies for PTSD comprise unclear risks of selection, detection and attrition biases, missing or incomplete information on blinding the assessors of the primary outcomes, small sample sizes, and heterogeneity both in the assessment and analysis of outcomes [2]. RCTs were rarely performed by researchers independent of the developers of the respective treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Previously published meta-analyses regarding psychological interventions for children and adolescents suffering from PTSD have largely focused on one specific intervention type, such as traumafocused cognitive behavior therapy (TF-CBT) or school-based interventions, or on a particular type of traumatic exposure, such as sexual abuse (Cary & McMillen, 2012;de Arellano et al, 2014;Harvey & Taylor, 2010;Kowalik, Weller, Venter, & Drachman, 2011;Lenz & Hollenbaugh, 2015;Macdonald et al, 2012). Silverman et al (2008) and Gillies, Taylor, Gray, O'Brien, and D'Abrew (2012) have meta-analyzed the efficacy of multiple psychological treatments for children and adolescents who have been exposed to different traumatic events. Silverman and colleagues included 21 randomized controlled trials (RCTs) in their meta-analysis and concluded that psychological interventions had positive, though modest, effects for PTSD symptoms and comorbid depression.…”
mentioning
confidence: 99%
“…Since the publication of the meta-analyses by Silverman et al (2008) and Gillies et al (2012), several RCTs on the efficacy of interventions for pediatric PTSD have been published (Carrion, Kletter, Weems, Berry, & Rettger, 2013;Danielson et al, 2012;Diehle, Opmeer, Boer, Mannarino, & Lindauer, 2015;Foa, McLean, Capaldi, & Rosenfield, 2013;Ford, Steinberg, Hawke, Levine, & Zhang, 2012;Jensen et al, 2014;McMullen, O'Callaghan, Shannon, Black, & Eakin, 2013;O'Callaghan, McMullen, Shannon, & Rafferty, 2015;O'Callaghan et al, 2014;O'Callaghan, McMullen, Shannon, Rafferty, & Black, 2013;Schottelkorb, Doumas, & Garcia, 2012;Tol et al, 2014). The goal of the present study was to provide an updated quantitative, meta-analytic review of the efficacy of interventions for children and adolescents suffering from PTSD.…”
mentioning
confidence: 99%